ANALISIS PENGENDALIAN RESIKO PADA USAHA KERIPIK SINGKONG - Pariyanti, Eka (Jurnal Manajemen Magister Darmajaya, 2017)
Risk control is a tool for entrepreneurs in decision-making processes to reduce or avoid the risks they face. The risk control applied by XYZ Chip Business must be effective in order to achieve the companys goals. The hope is that this XYZ Chipset Company can run its business by reaching high profits and guaranteed business continuity. The purpose of this research is to know and analyze risk control at XYZ cassava chips business. Data analysis was done by descriptive qualitative analysis using observation and interview. Qualitative descriptive analysis technique was used to analyze alternative risk control applied by business actor of XYZ chips. The results of the research shows that the most common risk is expired products on the market, then the company should give discounts one week before the cassava chip products are expired.Â Keywords: Risk,Control, Cassava Chip